2016
DOI: 10.3892/mmr.2016.5702
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic translocation of high-mobility group box-1 protein is induced by diabetes and high glucose in retinal pericytes

Abstract: The aim of the present study was to assess the involvement of the high-mobility group box-1 (HMGB1) protein, receptor for advanced glycation end products (RAGE) and nuclear factor (NF)-κB signaling pathway in the development of diabetic retinopathy. Rat primary retinal pericytes were exposed to 25 mmol/l D-glucose for 48 h. Diabetic retinal vessels were prepared from streptozotocin-induced diabetic rats 12 weeks following the induction of diabetes. The expression of HMGB1 was detected using immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…At the same time, NFκB expression also gradually increased. Recent findings suggest that the cytoplasmic translocation of HMGB1 may be caused by diabetes and high glucose in retinal pericytes, and that the pathogenic role of HMGB1 may be dependent on the expression of receptor for advanced glycation end product and activation of NFκB 33. In our study, IKKβ and NFκB protein expression was also decreased after inhibiting the expression of HMGB1.…”
Section: Discussionsupporting
confidence: 64%
“…At the same time, NFκB expression also gradually increased. Recent findings suggest that the cytoplasmic translocation of HMGB1 may be caused by diabetes and high glucose in retinal pericytes, and that the pathogenic role of HMGB1 may be dependent on the expression of receptor for advanced glycation end product and activation of NFκB 33. In our study, IKKβ and NFκB protein expression was also decreased after inhibiting the expression of HMGB1.…”
Section: Discussionsupporting
confidence: 64%
“…Microvascular injury of DR is well characterized and consists of a non-proliferative phase with occlusion of retinal vessels leading to ischemic retinal areas and macular edema, and in a proliferative phase characterized by increased vasopermeability and proliferation of retinal vessels and hemorrhages [120]. Different mechanisms are implicated in the pathogenesis of DR, specifically, generation of ROS and AGEs, activation of polyol and hexosamine pathways, enhanced cells apoptosis and release of cytokines (IL-1β, TNF-α), adhesion molecules (ICAM-1), leukocyte infiltration, abnormal expression of growth factors and activation of nuclear factors pathways [122,123]. All these factors promote alteration of retinal neurons and glial cells with impaired control of glutamate metabolism, impaired synaptic activity, neuronal apoptosis and activation of microglia with enhancement of inflammatory response [120].…”
Section: Hmgb1 and Diabetic Retinopathymentioning
confidence: 99%
“…Moreover, El-Asrar and coworkers demonstrated that levels of HMGB1 are higher in patients with PDR and retinal hemorrhages, suggesting a role of the protein in PDR progression [126]. The pro-inflammatory action of HMGB1 even in retinal cells is promoted by the linkage to TLR-4 [130,131] and RAGE [122,[131][132][133], and the activation of ERK1/2 and NF-kB signaling [132]. In fact, the intravitreal administration of the protein enhances these pathways and downregulates TLR-2 and occludin expression, enhancing retinal vasopermeability [134].…”
Section: Hmgb1 and Diabetic Retinopathymentioning
confidence: 99%
“…In vitro, AGEs or high glucose induced significant release of HMGB-1 from RGC-5 cells [56, 60]. Recently, cytoplasmic translocation of HMGB-1 was found in diabetes and high-glucose-induced retinal pericytes, which was dependent on RAGE/NF- κ B pathway [59]. In a clinical study, levels of HMGB-1 were positively correlated with monocyte chemoattractant protein-1 (MCP-1) and soluble intercellular adhesion molecule-1 (sICAM-1) in the vitreous fluid from patients with PDR, suggesting the role of HMGB-1 in inflammation of PDR [57].…”
Section: Hmgb-1 and Dr (Diabetic Retinopathy)mentioning
confidence: 99%